TECHNOLOGICAL SENTENCES OF HARMONIOUS UNITY OF TOLERANT, SPIRITUAL AND MENTAL ATMOSPHERE - THE BASIS OF THE DEVELOPMENT OF HUMAN VALUES (Pedagogy of Higher and Secondary Education, 2010)
The article deals with technologic maxims of the harmonious unity of the tolerant, spiritual and emotional atmosphere as the basis of the development of human values.
Keywords: technology; maxim; harmony; tolerance; spirituality; emotional; atmosphere; value